Phacomatosis pigmentovascularis of cesioflammea type - Delky Johanna Villarreal Villarreal; Fabiano Leal (Sociedade Brasileira de Dermatologia, 2016)
Abstract Phacomatosis pigmentovascularis is a rare syndrome, defined as the simultaneous presence of vascular nevus and melanocytic nevus in the same patient. We report the case of a 53-year-old woman presented with dermal melanosis and extensive vascular nevus, which match the typical manifestations of phakomatosis pigmetovascularis of cesioflammea type, according to Happle's classification. The rare occurrence of this genodermatosis and the clinical exuberance of the skin lesions motivated this case report.